Adjunctive Antimicrobial Photodynamic Treatment of Experimentally Induced Periodontitis in Rats With Ovariectomy. Issue 4 (1st April 2013) - Garcia, Valdir Gouveia; Gualberto Júnior, Erivan Clementino; Fernandes, Leandro Araújo; Bosco, Alvaro Francisco; Hitomi Nagata, Maria José; Casatti, Cláudio Aparecido; Ervolino, Edilson; Theodoro, Letícia Helena
Abstract : Background: The aim of this study is to compare antimicrobial photodynamic therapy (aPDT) as an adjunctive therapy to scaling and root planing (SRP) for the treatment of experimentally induced periodontitis in rats with ovariectomy (OVX) that are or are not treated with estrogen replacement. Methods: A total of 270 female rats were divided into three groups: 1) normal rats; 2) rats with OVX; and 3) rats with OVX with estrogen replacement. Periodontal disease was induced through the introduction of a cotton thread around the mandibular left first molar. After 7 days, the ligature was removed, and the rats were randomly divided into the following treatment groups: 1) SRP plus saline solution; 2) SRP plus low‐level laser therapy (LLLT); and 3) SRP plus toluidine blue O irrigation followed by LLLT. Ten rats from each group were euthanized at days 7, 15, and 30 after dental treatment. Bone loss (BL) in the furcation region was evaluated using histometric and immunohistochemical analyses. Results: aPDT treatment resulted in reduced BL compared with SRP treatment at all time points. Additionally, rats treated with aPDT exhibited reduced numbers of tartrate‐resistant acid‐phosphatase–positive cells and more proliferating cell nuclear antigen–positive cells in all treatment groups regardless of estrogen status. Whereas rats treated with aPDT showed weak immunoreactivity to the receptor activator of nuclear factor‐κ B ligand at day 7 post‐treatment, strong osteoprotegerin immunoreactivity was observed at day 15 post‐treatment. Conclusion: aPDT is an effective adjunctive therapy for the treatment of periodontitis in rats with OVX that are or are not given estrogen replacement therapy.